Teak Plantations in Thailand - Kushalappa, K. A. (Indian Forester, 1977)
Teak forests play a very significant role in the economy of Thailand, Regeneration of teak is moatly by artificial means (Plantations). Several operations are worth recognising. spedally the maintenance of permanent teak nurseries, storing or stumps before planting, creating forest villages and using machines wherever feasible. These aspects are described in detail.